Conservation and Preservation for Endangered Mangrove Species: Comprehensive Case Study of Swamp Forest on North Coast Area of Malaysia - Mona Fairuz Ramli; Ahmad Shabudin Ariffin; Marziah Zahar; Aizat Md Sin; Zuhud Rozaki (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Mangrove forests are special type of coastal ecosystem characterized by their adaptations that enable plants to thrive in saline soil. Despite accounting for only about 1% of global forest coverage, mangroves are keystone ecosystems that provide a variety of critical ecological processes and environmental services. In recent years, there has been a considerable increase in interest in mangrove biodiversity. The lack of community-based organizations (CBO) on the awareness of conservation has a direct negative impact on endangered species. The aim of this is to analyze the conservation and preservation for mangrove in north coast area of Malaysia. Qualitative method was used to collect and analyzed the data, and supported with observations. The findings showed that mangrove conservation project in Kilim and Acheh River rivers are participated by the different stakeholders such as local government units (LGU), NGOs (PiFWA and Koperasi Komuniti Kampung Kilim Langkawi Berhad and Koperasi Nelayan Sungai Kubang Badak Langkawi Berhad), as well as a local community composed of fishermen, gleaners and business operator (travel agent). Those stakeholders are playing different role depend on their capacities. This study proves that mangrove forests are important for coastal area in Malaysia, and conservation efforts are needed to protect it. This finding also can be applied in other area. The contribution and participation of all parties also need for any conservation activities. The funding is crucial for supporting the sustainability of conservation program because some parts of conservation need it to be built such infrastructure or material for conservation.